1986
DOI: 10.1001/archotol.1986.03780060022002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antibiotic Therapy on Recovery After Tonsillectomy in Children: A Controlled Study

Abstract: \s=b\ Tonsillectomycontinues to be a commonly performed operation in the pediatric age group. The postoperative period is often protracted and characterized by throat and ear pain, intermittent fever, foul odor from the oral cavity, and poor oral intake. Consequently, antibotics are frequently prescribed in an effort to minimize these symptoms and/or avoid complications such as dehydration or secondary infection of the operative site. However, to our knowledge, no study to date has been performed to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 6 publications
5
126
2
2
Order By: Relevance
“…Pain alleviation may prevent dehydration, mainly among younger children, and consequent hospitalization -often a traumatic experience for children and parents. 4 The patients in our trial did not require any medication other than the prescribed analgesics to manage their pain. Talbot 15 postulates that pain and sialorrhea in the post-op are more related to spasms in the pharyngeal constrictor muscles than to exposure of nerve endings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pain alleviation may prevent dehydration, mainly among younger children, and consequent hospitalization -often a traumatic experience for children and parents. 4 The patients in our trial did not require any medication other than the prescribed analgesics to manage their pain. Talbot 15 postulates that pain and sialorrhea in the post-op are more related to spasms in the pharyngeal constrictor muscles than to exposure of nerve endings.…”
Section: Resultsmentioning
confidence: 99%
“…Although antibiotics were deemed beneficial by some studies in relation to post-adenotonsillectomy morbidity 1,4 , one needs to consider the significant prevalence of adverse effects in the patient population 1,16 and, above all, the issue of bacterial resistance to antibiotics and the cost of treatment. Thus, the routine use of amoxicillin in post-adenotonsillectomy patients remains controversial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is based on early randomized control trials which suggested improved recovery with use of antibiotics. 5 Recent studies suggest that there is no role of antibiotics in reducing post tonsillectomy morbidity. 6 Cochrane review has not found any role of antibiotics in reducing incidence of post tonsillectomy secondary hemorrhage.…”
Section: Introductionmentioning
confidence: 99%